Utilizing Recycled concrete aggregate for treating Acid mine drainage - Elmira Brooshan; Tommi Kauppila; Małgorzata Szlachta; Mohammad Jooshaki; Jussi Leveinen (Cleaner Materials, 2023)
This study focuses on treating Acid Mine Drainage (AMD) using Recycled Concrete Aggregate (RCA) as a cost-effective and environmentally friendly material. RCA is utilized, considering its availability at low cost, to reduce heavy metal and sulfate concentration in AMD and neutralize its acidity in batch experimental mode. To that end, the adsorptive properties of RCA were characterized before and after adsorption by Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS), elemental mapping, Brunauer-Emmett-Teller (BET) surface area measurements, and X-ray Diffraction. Furthermore, the organic functional groups of the tested materials were identified by Fourier Transform Infrared Spectroscopy (FT-IR). Adsorption parameters such as dosage, contact time, the grain size distribution of adsorbent particles, and the solution pH, were optimized for enhancing the removal performance. The pH point of zero charges for the RCA sample was defined. The results revealed that RCA is a potential eco-friendly material for AMD treatment. The concentration of sulfate in the tested AMD water was reduced by approximately 84%, while that of the metal elements declined as follows: iron 100%, manganese 95%, copper 66%, zinc 97%, and lead 76%. Also, the pH value of AMD water increased rapidly and reached neutral by using small quantities of RCA (≤1g/L).